The History of the Ten "Lost" Tribes: Anglo-Israelism Examined - Baron, David (Salt Lake City, UT : Project Gutenberg, 2012)
"The History of the Ten 'Lost' Tribes: Anglo-Israelism Examined" by David Baron is a historical account likely written in the early 20th century. This work critically examines the theory of Anglo-Israelism, which posits that the British people are descendants of the Ten Lost Tribes of Israel, providing an analysis of the claims and scriptural interpretations that support this theory. The narrative aims to clarify misconceptions surrounding the fate of these tribes after the Assyrian captivity. The opening of the book serves as a preface, where the author explains his motivation for revisiting the subject of Anglo-Israelism. He recounts how this theory has often led to confusion among Christians and aims to debunk its various assertions through careful examination of relevant history and scripture. Baron outlines the structure of his treatise, indicating that he will address the claims of Anglo-Israelism in detail, deconstructing the arguments behind its interpretation of biblical texts, while highlighting the true historical context and consequences of the Ten Tribes' plight, ultimately asserting that the Jewish people fully represent the collective identity of Israel. (This is an automatically generated summary.)
Release date is 2012-01-20
Jason Isbell, Jeff G., and the Online Distributed Proofreading Team
Keywords: Jews -- History; Lost tribes of Israel; Anglo-Israelism